THE IMPACT OF SOCIAL MEDIA ON NURSING PRACTICE AND PROFESSIONAL DEVELOPMENT - Rubayyi Jeza Alsulami; Ahmad Thwab Al Nefaiei; Nawaf Awadhallah Aljuaid; Khamis Ayed Hamed Al Rubaie; Zaid Zowaid A Alsawat; Sami Hadi Jamil; Aqeelh Mohmmmed Albaharna; Aqeela Abdulrahman Aloqaili; Samah Hajie Alrizq; Fawaz Mohammed Alghamdi (Journal of Population Therapeutics and Clinical Pharmacology, 2022)
Social media has profoundly influenced the nursing profession, offering unprecedented opportunities for professional development, continuous learning, and public health advocacy. Platforms such as Facebook, Twitter, and LinkedIn facilitate the sharing of medical knowledge and best practices among healthcare professionals, enhancing the quality of patient care and enabling nurses to stay at the forefront of medical advancements. These digital tools also provide valuable networks for peer support, helping to alleviate feelings of professional isolation and reduce burnout by connecting nurses with their colleagues globally. However, the integration of social media in nursing also presents significant challenges, particularly in maintaining professionalism and patient privacy. The ease of information sharing can lead to breaches of confidentiality and the blurring of personal and professional boundaries, requiring vigilant management and adherence to ethical standards. Legal implications concerning privacy and professional conduct further complicate social media use, necessitating ongoing education and clear policies to guide nurses in their online activities. Moreover, social media serves as a powerful platform for public health communication and advocacy, enabling nurses to spread health awareness and engage in health policy discussions. During public health crises, such as the COVID-19 pandemic, social media proved invaluable for disseminating timely and critical information to the public. Nonetheless, the risk of misinformation remains a persistent threat, emphasizing the need for healthcare professionals to promote and disseminate accurate, evidence-based information. Addressing these issues requires a balanced approach that maximizes the benefits of social media while minimizing its risks. By developing comprehensive social media guidelines and providing training on ethical online behavior, healthcare institutions can empower nurses to use social media effectively and responsibly, ultimately enhancing their professional capabilities and the overall public health.